Magnetic Properties of Sm-Fe-N/Co-B Composite Magnets Prepared by Chemical Reduction - Tetsuji Saito (Advances in Condensed Matter Physics)
An attempt was made to produce Sm-Fe-N/Co-B composite magnets by chemical reduction. It was found that a composite powder consisting of Sm-Fe-N particles coated with fine Co-B particles could be obtained by chemical reduction. The Sm-Fe-N/Co-B composite powder acted as a single hard magnetic phase and showed a smooth hysteresis loop. The composite powder exhibited a higher remanence of 93.1 Am2/kg and a higher coercivity of 0.45 MA/m than a mixture of the Sm-Fe-N powder and Co-B powder prepared by a similar procedure but using a higher concentration of aqueous solution for the chemical reduction.